Penerapan Asuhan Keperawatan Pada Pasien Diabetes Melitus Tipe 2 di Ruang Flamboyan Rumah Sehat Untuk Jakarta RSUD Pasar Rebo: Studi Kasus - kartika; Gusrina Komara Putri (Politeknik Karya Husada, 2025)
Background: Type 2 diabetes mellitus is a chronic metabolic disease that may lead to various complications if not managed properly. Comprehensive nursing care is essential to optimize patients' clinical conditions and prevent complications. Objective: This study aimed to describe the implementation of nursing care for patients with type 2 diabetes mellitus in the Flamboyan Ward of Rumah Sehat untuk Jakarta RSUD Pasar Rebo in 2024. Methods: This study employed a descriptive case study design involving two patients diagnosed with type 2 diabetes mellitus. Data were collected through interviews, observation, physical examination, and documentation using a medical-surgical nursing care assessment format. The nursing process included assessment, nursing diagnosis, planning, implementation, and evaluation over a three-day period of care. Results: The findings revealed that both patients experienced several nursing diagnoses, including unstable blood glucose levels, acute pain, hypervolemia, and nausea. Following the implementation of standardized nursing interventions, both patients showed clinical improvement, as indicated by reduced symptoms and the achievement of most of the predetermined nursing outcomes. Conclusion: The implementation of standardized nursing care contributed to improving the clinical condition of patients with type 2 diabetes mellitus and supported disease management during hospitalization. Keywords: case study, nursing care, type 2 diabetes mellitus, hyperglycemia, complications.